Nonverbal Executive Functioning in Relation to Vocabulary and Morphosyntax in Preschool Children With and Without Developmental Language Disorder. - Everaert, Emma; Boerma, Tessel; Selten, Iris; Gerrits, Ellen; Houben, Michiel; Vorstman, Jacob; Wijnena, Frank (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Developmental language disorder (DLD) is characterized by persistent and unexplained difficulties in language development. Accumulating evidence shows that children with DLD also present with deficits in other cognitive domains, such as executive functioning (EF). There is an ongoing debate on whether exclusively verbal EF abilities are impaired in children with DLD or whether nonverbal EF is also impaired, and whether these EF impairments are related to their language difficulties. The aims of this study were to (a) compare nonverbal performance of preschoolers with DLD and typically developing (TD) peers, (b) examine how nonverbal EF and language abilities are related, and (c) investigate whether a diagnosis of DLD moderates the relationship between EF and language abilities. Method: A total of 143 children (nDLD = 65, nTD = 78) participated. All children were between 3 and 6.5 years old and were monolingual Dutch. We assessed nonverbal EF with a visual selective attention task, a visuospatial short-term and working memory task, and a task gauging broad EF abilities. Vocabulary and morphosyntax were each measured with two standardized language tests. We created latent variables for EF, vocabulary, and morphosyntax. Results: Analyses showed that children with DLD were outperformed by their TD peers on all nonverbal EF tasks. Nonverbal EF abilities were related to morphosyntactic abilities in both groups, whereas a relationship between vocabulary and EF skills was found in the TD group only. These relationships were not significantly moderated by a diagnosis of DLD. Conclusions: We found evidence for nonverbal EF impairments in preschool children with DLD. Moreover, nonverbal EF and morphosyntactic abilities were significantly related in these children. These findings may have implications for intervention and support the improvement of prognostic accuracy.